2016
DOI: 10.1155/2016/3592042
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage in Chronic Kidney Disease: Evaluation of Clinical Biomarkers

Abstract: Patients with chronic kidney disease (CKD) exhibit an increased cancer risk compared to a healthy control population. To be able to estimate the cancer risk of the patients and to assess the impact of interventional therapies thereon, it is of particular interest to measure the patients' burden of genomic damage. Chromosomal abnormalities, reduced DNA repair, and DNA lesions were found indeed in cells of patients with CKD. Biomarkers for DNA damage measurable in easily accessible cells like peripheral blood ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 102 publications
2
40
1
Order By: Relevance
“…11,12 In addition, recent evidence has also suggested that patients with CKD and ESRD have deoxyribonucleic acid (DNA) damage and impaired DNA repair, potentially leading to an increased cancer risk. 45 In our meta-analysis, we demonstrated that the incidence of kidney cancer was 0.4% in ESRD patients, which is significantly higher than the currently reported incidence (approximately 0.005%) in the general population. 5 While the association between ESRD and urothelial cancers could be hypothesized as ACKD related, we lack a clear understanding for the high incidence of urothelial cancers in the ESRD population.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…11,12 In addition, recent evidence has also suggested that patients with CKD and ESRD have deoxyribonucleic acid (DNA) damage and impaired DNA repair, potentially leading to an increased cancer risk. 45 In our meta-analysis, we demonstrated that the incidence of kidney cancer was 0.4% in ESRD patients, which is significantly higher than the currently reported incidence (approximately 0.005%) in the general population. 5 While the association between ESRD and urothelial cancers could be hypothesized as ACKD related, we lack a clear understanding for the high incidence of urothelial cancers in the ESRD population.…”
Section: Discussionmentioning
confidence: 52%
“…Regardless of its association with renal function, ACKD is a known risk factor for kidney cancer . In addition, recent evidence has also suggested that patients with CKD and ESRD have deoxyribonucleic acid (DNA) damage and impaired DNA repair, potentially leading to an increased cancer risk . In our meta‐analysis, we demonstrated that the incidence of kidney cancer was 0.4% in ESRD patients, which is significantly higher than the currently reported incidence (approximately 0.005%) in the general population …”
Section: Discussionmentioning
confidence: 98%
“…It is well known that CKD patients present an elevated incidence of different types of cancer (mainly cervical, bladder, thyroid, and renal), as well as cardiovascular pathologies (Di Angelantonio et al, 2010;Stengel, 2010). With regard to the comet assay this has been demonstrated to be a potent tool in human biomonitoring studies (Collins et al, 2014), and it has been already used to evaluate genetic damage levels in CKD patients (Corredor et al, 2015;Schupp et al, 2015;Mamur et al, 2016). Previous studies have demonstrated increased levels of DNA damage and genomic instability in CKD patients (Sandoval et al, , 2012Stoyanova et al, 2010Stoyanova et al, , 2014Rodr ıguez-Ribera et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It must be remembered that the frequency of MN is considered one of the best and most reliable biomarkers to detect genotoxic agents (Kirsch-Volders et al, 2014), and it has been widely used for the study of chronic renal failure patients (Roth et al, 2008;Sandoval et al, 2012;Rodr ıguez-Ribera et al, 2014). With regard to the comet assay this has been demonstrated to be a potent tool in human biomonitoring studies , and it has been already used to evaluate genetic damage levels in CKD patients (Corredor et al, 2015;Schupp et al, 2015;Mamur et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated frequencies of MNi are also found in patients with cancer and other diseases [3,4]. MNi are formed from an entire chromosome or from a chromosomal fragment.…”
Section: Introductionmentioning
confidence: 99%